How to Measure Whether Index Insurance Provides Reliable Protection - Morsink, Karlijn; Clarke, Daniel Jonathan; Mapfumo, Shadreck (World Bank, Washington, DC, 2016)
Agricultural index insurance offers the promise of an affordable and sustainable insurance product for farmers that can help reduce their vulnerability to aggregate agricultural shocks such as large-scale drought or flooding. However, index insurance provides claim payments based on a trigger that is only imperfectly correlated with losses. This implies that it carries basis risk: it may provide claim payments in years when there are no losses, and no claim payments in years when there are losses. The impact of index insurance on poverty outcomes is highly sensitive to the degree to which the product offers reliable protection. Offering unreliable index insurance may lead to high reputation risk for donors, governments, and the private sector. This study proposes to measure the reliability of index insurance in terms of two policy objectives that stakeholders may have when offering index insurance: the extent to which the insurance captures losses caused by the peril covered by the contract (insured peril basis risk) and the extent to which the insurance covers losses from agricultural production (production smoothing basis risk). For both types of basis risk two indicators are proposed: the probability of catastrophic basis risk and the catastrophic performance ratio. Donors, governments, and insurers can use the proposed monitoring indicators without much prior technical knowledge. Although the indicators specifically focus on agricultural index insurance for low-income farmers, they can be applied to any context where payments are provided based on indices that are correlated with losses.